Seasonality Structures Avian Functional Diversity and Niche Packing Across North America - Keyser, Spencer R.; Pauli, Jonathan N.; Fink, Daniel; Radeloff, Volker C.; Pigot, Alex L.; Zuckerberg, Benjamin (Ecology letters, 2024)
ABSTRACT Assemblages in seasonal ecosystems undergo striking changes in species composition and diversity across the annual cycle. Despite a long‐standing recognition that seasonality structures biogeographic gradients in taxonomic diversity (e.g., species richness), our understanding of how seasonality structures other aspects of biodiversity (e.g., functional diversity) has lagged. Integrating seasonal species distributions with comprehensive data on key morphological traits for bird assemblages across North America, we find that seasonal turnover in functional diversity increases with the magnitude and predictability of seasonality. Furthermore, seasonal increases in bird species richness led to a denser packing of functional trait space, but functional expansion was important, especially in regions with higher seasonality. Our results suggest that the magnitude and predictability of seasonality and total productivity can explain the geography of changes in functional diversity with broader implications for understanding species redistribution, community assembly and ecosystem functioning. Seasonality prompts the large‐scale redistribution of species, generating dynamic patterns of biodiversity. Using seasonally explicit bird species distribution models we demonstrate that various aspects of environmental seasonality explain seasonal dynamics of functional diversity. Further, we find seasonal increases in species richness are primarily accommodated by niche packing, but the role of niche expansion increases with the magnitude of seasonality.